2021
DOI: 10.1016/j.cub.2021.06.076
|View full text |Cite
|
Sign up to set email alerts
|

Ovulation suppression protects against chromosomal abnormalities in mouse eggs at advanced maternal age

Abstract: Highlights d Ovulation reduction protects against Rec8 loss and egg aneuploidy in aged female mice d Ovulations contribute to physiological aging of oocytes and the maternal age effect d Cellular aging is associated with changes in 3D chromatin organization d Cohesin complexes mediating sister chromatid cohesion restrict loop extrusion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 90 publications
2
17
0
Order By: Relevance
“…Although the mechanism of bypassing obstacles is not known, it is conceivable that a topological engagement of proteins around DNA could interfere with cohesin binding to DNA to ‘swing over’ a protein 46 . Consistent with this, cohesin that topologically entraps sister chromatids restricts loop extrusion mediated by other cohesin complexes in oocytes 32 , 47 . In addition, the YDF disordered region alters the outcome of cohesin–MCM collisions from blocking to pausing, which suggests that MCMs are active chemical barriers with binding sites rather than passive physical barriers.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Although the mechanism of bypassing obstacles is not known, it is conceivable that a topological engagement of proteins around DNA could interfere with cohesin binding to DNA to ‘swing over’ a protein 46 . Consistent with this, cohesin that topologically entraps sister chromatids restricts loop extrusion mediated by other cohesin complexes in oocytes 32 , 47 . In addition, the YDF disordered region alters the outcome of cohesin–MCM collisions from blocking to pausing, which suggests that MCMs are active chemical barriers with binding sites rather than passive physical barriers.…”
Section: Discussionsupporting
confidence: 63%
“…snHi-C was carried out as previously described 27 , 28 , 32 , 47 . Pronuclei of wild-type, Scc1 Δ/Δ , Wapl Δ/Δ and Zp3-dsCTCF zygotes were fixed around 1.5 h after visualization of pronuclei (corresponding to 6–6.5 h after fertilization) and therefore are expected to be in G1 phase of the cell cycle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that two separate populations of Rec8 cohesin act on loop formation and cohesion [ 34 ]. In mouse oocyte meiosis, it has been suggested that RAD21/SCC1 and REC8 cohesins have distinct functions in chromatin loop formation and cohesion, respectively [ 36 , 108 ]. Functions of the kleisin subunits in meiotic chromatin structure may differ among species.…”
Section: Roles Of Meiotic Cohesin In Chromosome Architecturementioning
confidence: 99%
“…Even in asynaptic organisms, Rec8 cohesin forms an axial structure resembling the lateral element, which is essential for homologous recombination during meiosis [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. In addition to these canonical roles of Rec8 cohesin in recombination, recent developments in technologies, such as genome-wide chromosome conformation capture, have revealed roles for Rec8 cohesin in meiotic chromosome architecture [ 33 , 34 , 35 , 36 ]. This review highlights the role of Rec8 cohesin in meiosis, which is common in both SC-forming and asynaptic organisms.…”
Section: Introductionmentioning
confidence: 99%